Historical phonology in service of subgrouping. Two laws of final syllables in the common prehistory of Baltic and Slavonic - Hill, Eugen (Baltistica, 2013)
The traditionally assumed intermediate Balto-Slavonic stage after the break up of Proto-Indo-European can be additionally supported by two highly specific and thus potentially exclusive developments at the end of a word. The first development is the loss of the PIE word-final short *i after a long vowel followed by a labial consonant. This sound change must have occurred later than the secondary shortening of long vowels before word-final PIE *m which is shared by Celtic. The second sound law is the raising of stressed PIE *o to *u in word-final position before consonants both in Baltic and Slavonic. The postulated sound changes are established by means of an in deep analysis of the relevant endings in the inflection of Baltic and Slavonic nouns, pronouns and adjectives.